Calcification of Human Saphenous Vein Associated with Endothelial Dysfunction: A Pilot Histopathophysiological and Demographical Study - Pedigo, Sydney L.; Guth, Christy M.; Hocking, Kyle M.; Banathy, Alex; Li, Fan Dong; Cheung-Flynn, Joyce; Brophy, Colleen M.; Guzman, Raul J.; Komalavilas, Padmini (Frontiers in Surgery, 2017)
While the pathophysiology and clinical significance of arterial calcifications have been studied extensively, minimal focus has been placed on venous calcification deposition. In this study, we evaluated the association between calcium deposition in human saphenous vein (HSV), endothelial function, and patient demographic risk factors. Fifty-four HSV segments were collected at the time of coronary artery bypass graft (CABG) surgery. The presence or absence of calcium deposits was visualized using the Von Kossa staining method. Endothelial function was determined by measuring muscle tissue contraction with phenylephrine and relaxation with carbachol in a muscle bath. Additional segments of vein underwent histologic evaluation for pre-existing intimal thickness, and extracellular matrix (ECM) deposition. Patient demographics data were obtained through our institution’s electronic medical record, with patient consent. Calcium was present in 16 of 54 samples (29.6%). Veins with calcium deposits had significantly greater intimal-to-medial thickness ratios (p = 0.0058), and increased extracellular collagen deposition (p = 0.0077). Endothelial relaxation was significantly compromised in calcified veins versus those without calcium (p = 0.0011). Significant patient risk factors included age (p=0.001) and preoperative serum creatinine (p=0.017). Calcified veins can be characterized as having endothelial dysfunction with increased basal intimal thickness, and increased ECM deposition. Patient risk factors for calcium deposits in veins are similar to those for arteries, namely advanced age and kidney disease. Further studies are needed to determine the effect of pre-existing vein calcification on short and long-term graft patency.